Practice of building integrated photovoltaic (BIPV) in domestic building / Mohd Hafiz Md Izuddin (Faculty of Architecture, Planning and Surveying, 2008)
Solar photovoltaic is a clean form of renewable energy which the technology converts sunlight directly to electricity. The technology is widely adopted by countries such as Germany, Japan and the United States. For Japan, by the year 2005, 253,754 homes had PV system or photovoltaic installed through their capital subsidy programme. Germany boasted the world’s highest PV installed capacity with 2,863 MW in 2006 with the growth largely due to the attractive feed-in tariff as a result of the passing of Renewable Energy Source Act. For Malaysia, the abundance and consistent sunlight makes this renewable energy technology most suitable for urban applications. Building Integrated Photovoltaic (BIPV) is which the building that has provided together with the solar system that is can generate the electricity through the solar panel. Photovoltaic system used the solar irradiance to electricity with solar panel. The electricity that generated depends on the efficiency of solar panels. In Malaysia, solar industry was introduced in early 1980’s, primarily to provide basic electricity to remote areas. In July 1998, the solar system or photovoltaic has installed at the University Kebangsaan Malaysia for Malaysia’s first practical experience of grid-connected PV on the initiative if the notional power utility.